Aplikasi Mobile untuk Sistem Antrian Praktek Dokter Dilengkapi dengan Analisis Perhitungan Estimasi Waktu Menggunakan Markov Chain dan Algoritma PageRank: Analisis Perhitungan Estimasi Waktu Menggunakan Markov Chain dan Algoritma PageRank - Cato Chandra; David Sanjaya; Julio Narabel; Nucky Vilano; Setia Budi (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
Along with the increasingly rapid development of technology, especially in the field of computers, ways to overcome the problem of patient queues have been developed. One of them is the use of a mobile application to get a time estimate until a patient gets a turn to consult with a doctor. Many industries still use manual methods to overcome this queue problem. Based on this fact, this final project with title "Mobile Applications for Doctor Examination Queue System Equipped with Analysis of Time Estimation Calculation Using the Markov Chain and PageRank Algorithm" has aims to get time estimates for the patients so that time can be more efficient.